THE INFLUENCE OF SELF-CONFIDENCE ON THE MATHEMATICAL REASONING ABILITY OF JUNIOR HIGH SCHOOL STUDENTS - Hasna Salsabilla Jati; Joko Soebagyo (FKIP Universitas Muhammadiyah Tangerang, 2023)
Self-confidence is an aspect of personality that plays a role in shaping the potential of students, if they master the confidence with slick, it is also expected to pursue their mathematics to produce optimal results, so that this aspect also has an influence as an important role in the ability of mathematical reasoning students. This study has the intention to see the effect of student confidence on the mathematical reasoning ability of Grade IX students of SMPN 11 Bekasi semester 1 of the 2022-2023 academic year. The proposed research method is quantitative research techniques with survey research design. The sampling technique used is Simple Random Sampling. The population of Class IX was 237 students. Samples were taken as many as 149 students using the Slovin formula. The research Data was obtained through testing instruments about mathematical reasoning ability as much as 5 points and instrument questionnaire confidence as much as 20 statements. The results obtained can be concluded in the form of self-confidence affect the reasoning ability of students. Self-confidence had a positive effect of 3.4% on students ' reasoning ability. however, students ' self-confidence is still at a moderate level. So, the reasoning ability of students cannot be said to be optimal. Based on the results found, it is necessary to conduct extended research on this theme by using various other influencing factors.